How Does the Scientific Approach Matter to School Students' Higher Level Thinking Ability? - Mariana Lestari; Komang Sutawan; Widiyanto Widiyanto (Universitas Sebelas Maret, 2024)
The research was conducted to find the effect of the practice of scientific views on the ability of high-level of students in thinking. The problems that occur to students are that there are students who are passive in question-and-answer sessions during the learning process or raise questions from learning videos and subject matter, there are students who are not creative in analyzing a case according to the learning topic, there are students who live with way of think issue at a learning process at class with high level thinking, there are some students do not know how to apply the way to analyze and evaluate in the Buddhist education subjects. Learning with a scientific approach can bring the impact to learning through the systematic and holistic thinking practices. This research brought the approach of quantitative and developed a survey method. The respondents is in total 70 people. The research place has been done at Buddhist School in Jakarta City. The data analysis result showed that can be interpreted that the scientific approach positively affected of student in thinking ability with high-level standard. The result recommendation to bring the perspective of the ability of school students in high-level thingking to create a tremendous way of learning in thinking level at class, so the schools and government can formulate the proper policy in school national standard and criteria. The research is limited in research time and methodology development, for new researchers can manage the time to explore more detail and concrete in the data collection using a direct observation and case study procedure in qualitative approach.